From Classic to Classy: Changing Fashions in Street Names - John Algeo (Names, 2015)
Street names in Athens, Georgia, are of two kinds: older, traditional, central, commemorative, directional = “classic,” and newer, innovative, suburban, evocative, given by real-estate developers for their commercial appeal = “classy.” The city of Athens is the site of the University of Georgia, the State Botanical Garden, the Georgia Museum of Art, and notably a double-barreled cannon, which was supposed to fire two chain-linked cannon balls simultaneously, but which succeeded on its trial shot only in demolishing a fence and killing a cow. The city was consolidated with Clarke County, yielding a population of some 120,000.